Breaking the rules in interactive media design education - Ozcan, Oguzhan; Yantac, Asim Evren; O'Neil, Mary Lou (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2009)
In today's interactive media design it is difficult for a designer to create aesthetic innovations and to break free from ordinariness. The most important factor limiting interactive media design aesthetics is that education seems to be more focused on following traditional rules of interaction design rather than innovative approaches. These rules limit creativity and often relegate design students to producing ordinary interface solutions. This is especially burdensome for us as teachers. In order to address this problem, we developed an education model inspired by Lars von Trier's film Five Obstructions. We call this model 'breaking the rules'. In the 'breaking the rules' approach students produce, within a range of probabilities, design problem solutions in cases of total or partial visual/auditory/tactile obstructions. The most important outputs of the model are (1) to make design student think/look outside of the ordinary, (2) to produce unusual solutions, (3) to maximise design solutions with sound.
Keywords: interactive media; design education; creativity; breaking rules; innovation; Art